Through the flow guide portal structure to isolate the cold airflows to improve the cold resistance of the tunnel - Ke Yin; Rui Wang; Licai Zhao; Lei Wang; Songli Chen; Yinlei Wang (Alexandria Engineering Journal)
Isolating cold air within a tunnel is an effective method for mitigating freezing damage. In this study, a flow guide open tunnel structure (FGOT) was developed as a solution to effectively isolate cold airflows without consuming additional energy. The airflow fields in an open cut tunnel (OCT) and the FGOT were analyzed using a scale model test to verify the FGOT’s ability to block cold air. The anti-freezing performance of the FGOT was also evaluated numerically based on Xinbin Tunnel as a case study. The results indicate that FGOT effectively prevents cold airflows from entering the tunnel. When the angle between the incoming wind direction and the tunnel’s transverse axis does not exceed 45°, an FGOT with a length of 30 m can completely block cold airflows. Regardless of wind direction, the FGOT exhibits a significantly greater capacity to block cold airflows compared to the OCT. In the presence of a portal structure or with only an OCT in place, significant low-temperature zones develop. The FGOT reduces the extent of low-temperature zones in the surrounding rock; this area decreases further as the length of the FGOT increases. These qualities allow the FGOT to significantly enhance the cold resistance of tunnels.